ONLINE DELIVERY, DINE-IN, AND RESERVATION SYSTEM USING THROW-AWAY PROTOTYPING AT JONG JAVA RESTAURANT - Rahmawati, Titasari; Trianto, Edwin Meinardi; Tjipta, William Eka (LPPM Universitas Nusa Mandiri, 2025)
The culinary industry continues to grow amidst the increasing purchasing power and consumption of society. Many restaurants still rely on direct sales (dine-in) without utilizing technology to enhance services and expand their market. This study aims to design and build a web-based information system for Restoran Jong Java, which includes dine-in, online delivery, and table reservation features. The system is expected to simplify transaction processes, improve operational efficiency, and provide added value for the restaurant in the industry competition. The system is developed using the throw-away prototyping method. This method allows for iterative system development with direct input from users. Testing is conducted using black-box testing to ensure the system functions as per the specifications, and user acceptance testing is performed through questionnaires with five main types of users: customers, admins, cashiers, waiters, and waitresses. The designed system is capable of supporting the integrated management of dine-in services, reservations, and online deliveries. The tests show that the system meets user needs, with a high level of satisfaction from the respondents. The user acceptance testing in this study shows positive results across different user groups. For the customer group, the average score obtained was 77.25%, the waiter group gave an average score of 83.6%, and for the managers, the system was also well received by them. This system has successfully improved the restaurant's operational efficiency and provided convenience for customers in making orders. It also serves as a technological solution that can help Jong Java expand its market reach and increase competitiveness.